MARKETING MIX STRATEGY AND SWOT EVALUATION TO IMPROVE MARKETING PERFORMANCE AT MOMOCI DESSERT MSMES - Fadhillah, Yosi; Pangestu, Mira Gustiana; Sabrina, Hanan Laras; Yossinomita, Yossinomita (Journal of Business Studies and Management Review, 2024)
Momoci Dessert, a culinary UMKM, faces difficulties in maintaining and improving marketing performance amidst increasingly tight competition. The purpose of this study is to evaluate the marketing mix strategy (four Ps: product, price, place, and promotion) along with SWOT (Strengths, Weaknesses, Opportunities, and Threats) evaluation. The purpose of this analysis is to create a strategic plan that can improve marketing performance. This study was conducted descriptively qualitatively, and data were collected through observation, document analysis, and interviews. The results showed that Momoci Dessert's new flavor variations (strawberry, mango, and chocolate) and the use of social media as the main promotional tool succeeded in attracting customers. However, the SWOT analysis showed that promotions and threats from larger competitors were inconsistent. Increasing local snack trends can help expand market share. This study found that creative marketing mix strategies and proper SWOT analysis can help optimize the marketing performance of MSMEs. This study is also expected to provide practical insights for other MSMEs facing similar problems.